CYBER THREATS AND THE ROLE OF CRYPTO CURRENCIES IN THE FINANCING OF TERRORISM (Third Sector Social Economic Review, 2022)
Terrorists need funding to recruit and support militants, set up and manage logistics centers, and run operations. In this context, terrorist groups widely use the internet and virtual world to finance their activities. They obtain significant financial resources by collecting donations directly on the Internet, conducting electronic commerce, conducting online gambling activities, manipulating online payment systems, stealing digital currency, selling drugs and illegal products on the Dark Web, or exploiting charity-like structures. The technological opportunities provided by the Internet and mobile technologies also help terrorist organizations to launder money. Cryptocurrencies like Bitcoin or virtual currencies like the Linden Dollar allow these organizations to transfer money secretly. In this study, the role of cyber threats and cryptocurrencies in financing and combating terrorism is analyzed. This study examines the impact of cryptocurrency on terrorism financing through secondary data collection from various articles, research studies and websites. Since cryptocurrencies are decentralized currencies and there is great anonymity in their operation, its usage is quite difficult to track. This makes it difficult to conduct a primary database search in the study. Therefore, in this study, the evaluation of the relationship between terrorist financing and crypto money is made with publicly available information.
Keywords: Financing of Terrorism; International Security; Crypto Currencies; Cyber Threats